Percentage of Local Sheep Carcases: Feed by Fermented Cassava Peel - Yunilas; Tati Vidiana Sari; Edhy Mirwandhono; Sayed Umar; M. Fadil (Jurnal Peternakan Integratif, 2022)
This study aimed to determine the effect of giving various doses of fermented cassava peel by local microorganisms (MOL) on the percentage of carcasses of local male sheep. The research was carried out at Mr. Praditya Raharja's Ranch, Jalan Bunga Rinte, Simpang Selayang, Medan, from December 16, 2019 to March 8, 2020 using a completely randomized design (CRD) with 4 treatments and 5 replications. This study used 20 male local sheep with an average initial body weight of 12.59 Â± 1.22 kg. The treatments were: P0 (without fermented cassava peel in the ration), P1 (25% fermented cassava peel in the ration), P2 (50% fermented cassava peel in the ration), and P3 (75% fermented cassava peel in the diet). ration). The parameters studied were final weight, slaughter weight, empty body weight, and carcass percentage. The results showed that the application of cassava peel fermented by MOL in the ration had no significant effect (P>0.05) on the final weight (P0=26.17 kg/head, P1=23.34 kg/head, P2=24.50 kg/head, P3=23.43 kg/head), slaughter weight (P0=26.10 kg/head, P1=22.67 kg/head, P2=24.23 kg/head, P3=22.38 kg/head), body weight empty (P0=18.81 kg/head, P1=17.20 kg/head, P2=18.37 kg/head, P3=16.64 kg/head), carcass weight (P0=11.31 kg/head , P1=9.55 kg/head P2=10.15 kg/head, P3=9.27 kg/head), and carcass percentage (P0=60.17%, P1=55.16%, P2=55, 17%, P3=55,70%). The conclusion of this study was that giving fermented cassava peel to sheep still had a positive effect, as it did not reduce the body weight of the sheep's carcass and the percentage of carcass produced was more than 50%.